2013
DOI: 10.1167/13.12.20
|View full text |Cite
|
Sign up to set email alerts
|

The ventriloquist in periphery: Impact of eccentricity-related reliability on audio-visual localization

Abstract: The relative reliability of separate sensory estimates influences the way they are merged into a unified percept. We investigated how eccentricity-related changes in reliability of auditory and visual stimuli influence their integration across the entire frontal space. First, we surprisingly found that despite a strong decrease in auditory and visual unisensory localization abilities in periphery, the redundancy gain resulting from the congruent presentation of audio-visual targets was not affected by stimuli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 67 publications
(72 reference statements)
9
29
2
1
Order By: Relevance
“…Electrophysiological and human psychophysics studies have taken the first steps in the investigation of cross-modal interactions of visual and auditory stimuli in the peripheral visual field (Wang et al, 2008;Charbonneau et al, 2013;Gleiss and Kayser, 2013). The effect of attention is another direction that has produced promising results (Jack et al, 2006;Cate et al, 2009).…”
Section: The Functions Of the Far Peripheral Visual Fieldmentioning
confidence: 99%
“…Electrophysiological and human psychophysics studies have taken the first steps in the investigation of cross-modal interactions of visual and auditory stimuli in the peripheral visual field (Wang et al, 2008;Charbonneau et al, 2013;Gleiss and Kayser, 2013). The effect of attention is another direction that has produced promising results (Jack et al, 2006;Cate et al, 2009).…”
Section: The Functions Of the Far Peripheral Visual Fieldmentioning
confidence: 99%
“…Both auditory (Mills, 1958; Makous and Middlebrooks, 1990; Charbonneau et al , 2013; Wood and Bizley, 2015; Carlile et al , 2016) and visual localisation acuity declines with eccentricity (Mateeff and Gourevich, 1984; Perrott et al , 1993; Charbonneau et al , 2013). Few studies have attempted to directly compare spatial acuity for auditory and visual stimuli throughout the visual field and focus instead on the spatial capture observed when spatially separated auditory-visual signals are presented (Howard and Templeton, 1966; Bertelson and Radeau, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, Charbonneau, Veronneau, Boudrias-Fournier, Lepore, and Collignon (2013) found that the visual capture of spatially misaligned auditory information in human adults declines with eccentricity, suggesting that adults do reduce their reliance on vision in audio-visual peripheral spatial decisions.…”
Section: Introductionmentioning
confidence: 95%